2021
DOI: 10.2118/208615-pa
|View full text |Cite
|
Sign up to set email alerts
|

Dimethyl Ether as a Novel Solvent for Bitumen Recovery: Mechanisms of Improved Mass Transfer and Energy Efficiency

Abstract: Summary A solvent-based thermal recovery process has the advantages of low capital expenditure, less energy consumption, and less greenhouse gas emission. Dimethyl ether (DME), as a renewable solvent, has been considered as a novel additive in the thermal bitumen recovery process. Being soluble in both water and oil phases, DME has the potential to enhance mass transfer and improve oil production. In this work, a phase behavior model of the DME-bitumen-water system is first developed considering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 58 publications
1
9
0
Order By: Relevance
“…As a consequence, the impact of numerical diffusion/dispersion on the numerically simulated steam chamber ramp-up phase could be neglected by applying the grid size of 5.0 cm × 5.0 cm. The findings were consistent with the results of previous studies in that millimeter-sized grids led to an accurate numerical diffusion/dispersion for the representation of the physical process [47]. Thus, to obtain an efficient simulation model, the grid size of 5.0 cm × 5.0 cm (scenario 2) was chosen as the base grid size.…”
Section: Effects Of Grid Size On Simulation Performancesupporting
confidence: 86%
See 3 more Smart Citations
“…As a consequence, the impact of numerical diffusion/dispersion on the numerically simulated steam chamber ramp-up phase could be neglected by applying the grid size of 5.0 cm × 5.0 cm. The findings were consistent with the results of previous studies in that millimeter-sized grids led to an accurate numerical diffusion/dispersion for the representation of the physical process [47]. Thus, to obtain an efficient simulation model, the grid size of 5.0 cm × 5.0 cm (scenario 2) was chosen as the base grid size.…”
Section: Effects Of Grid Size On Simulation Performancesupporting
confidence: 86%
“…In the numerical reservoir simulation of the SAGD process, it was essential to apply sufficiently fine grids for the accurate estimation of the steam chamber [46]. Recent work on the effects of grid dimensions on thermal oil recovery simulation has further indicated that a fine grid system eliminates the impact of numerical diffusion on the numerical estimation, which is caused by the discretization in space and time [47]. In this work, a field-scale numerical simulation model with fine grids was built to investigate the multiphase fluid flow mechanisms and dynamic steam chamber expansion during the ramp-up phase of an SAGD process.…”
Section: Fine Grid Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Usually numerical simulation is used as a powerful tool to predict oil recovery performance and design operational parameters for many different process and geological scenarios. 89,90 However, simulation of an ISC process is very complicated mainly associated with the complex chemical reactions involved and three-phase fluid flow in the presence of noncondensable gases.…”
Section: Reaction Kinetics Model 311 Development Of the Kinetic React...mentioning
confidence: 99%